Diagnosis of pneumonia and malaria in Nigerian hospitals: A prospective cohort study. Issue 1 (19th February 2020) - Graham, Hamish; Bakare, Ayobami A.; Ayede, Adejumoke I.; Oyewole, Oladapo B.; Gray, Amy; Neal, Eleanor; Qazi, Shamim A.; Duke, Trevor; Falade, Adegoke G.
Abstract: Background: Pneumonia and malaria are the leading causes of global childhood mortality. We describe the clinical presentation of children diagnosed with pneumonia and/or malaria, and identify possible missed cases and diagnostic predictors. Methods: Prospective cohort study involving children (aged 28 days to 15 years) admitted to 12 secondary‐level hospitals in south‐west Nigeria, from November 2015 to October 2017. We described children diagnosed with malaria and/or pneumonia on admission and identified potential missed cases using WHO criteria. We used logistic regression models to identify associations between clinical features and severe pneumonia and malaria diagnoses. Results: Of 16 432 admitted children, 16 184 (98.5%) had adequate data for analysis. Two‐thirds (10 561, 65.4%) of children were diagnosed with malaria and/or pneumonia by the admitting doctor; 31.5% (567/1799) of those with pneumonia were also diagnosed with malaria. Of 1345 (8.3%) children who met WHO severe pneumonia criteria, 557 (41.4%) lacked a pneumonia diagnosis. Compared with "potential missed" diagnoses of severe pneumonia, children with "detected" severe pneumonia were more likely to receive antibiotics (odds ratio [OR], 4.03; 2.63‐6.16, P  < .001), and less likely to die (OR, 0.72; 0.51‐1.02, P  = .067). Of 2299 (14.2%) children who met WHO severe malaria criteria, 365 (15.9%) lacked a malaria diagnosis. Compared with "potential missed" diagnoses of severe malaria, children with "detected" severe malaria were less likely to die (OR, 0.59; 0.38‐0.91, P  = 0.017), with no observed difference in antimalarial administration (OR, 0.29; 0.87‐1.93, P  = .374). We identified predictors of severe pneumonia and malaria diagnosis. Conclusion: Pneumonia should be considered in all severely unwell children with respiratory signs, regardless of treatment for malaria or other conditions.